Menu Engineering on Food to Increase Revenue at Laku Café, Gading Serpong - Sherlen Frelinsia Goh; Wiwik Nirmala Sari (CV. Syntax Corporation Indonesia, 2023)
The Food and Beverage industry is an industry that has existed and developed for a long time until now. The Food and Beverage sector is engaged in the manufacture and serving of food and beverages and also provides services to customers. Merdeka (2022) emphasizes that Food and Beverage is a part of hospitality that is centered on food and beverage services which aims to achieve customer satisfaction. The method used is descriptive research with a qualitative approach. Research data collection was carried out using documentation studies to determine the level of menu profitability using a menu engineering system. Based on the results of the analysis, it can be concluded that among the menu items sold, there are several menu items that are less popular and there are also menus that bring low profits. There are many ways to increase revenue, including: increasing the attractiveness of the menu, increasing menu prices by switching to cheaper raw materials with the same quality, reducing portion sizes or creating combination packages with other menus that have low costs, removing several menus from the list. menu.